A novel double slip loads friction damper to control the seismic response of structures. (15th December 2020) - Ghorbani, Hamid R.; Rofooei, Fayaz R.
Highlights: Controlling structural response under two seismic intensity levels input. Providing extra stiffness under intense excitations by a 2 nd stiffening phase. Reducing the base shear force by adjusting the lateral stiffness. Producing a more uniform drifts and accelerations along the building height. Developing the hysteresis behavior of a novel double slip load friction damper. Abstract: In this study, the performance of a proposed friction damper with two slip loads in controlling the seismic response of steel moment resisting buildings structures under moderate and intense earthquake excitations is investigated. The proposed friction damper initially operates with a smaller slip load and could shift to the higher slip load after a certain amount of slippage when subjected to intense ground motions. In this regard, the hysteresis behavior of the proposed double slip loads (DSL) friction damper is modeled and after necessary verifications is imported to the material library of OpenSees software to be used for parametric study. To evaluate the performance of the proposed DSL damper, three steel moment resisting frame (SMRF) models with 4, 8 and 14 stories are considered that are designed according to the AISC-LRFD and ASCE7-16 codes. Using a suite of earthquake records, nonlinear time history analyses (N-THA) are carried out to determine the optimal slip loads as well as the optimal amount of the slippage in between to minimize the seismic response of the considered models. The smaller slip load is optimally determined by performing N-THA on the structural models equipped with a single slip load friction damper using the earthquake records that are scaled to the design basis earthquake (DBE) level. Then, utilizing the obtained first slip load, N-THA are repeated for the models equipped with DSL friction dampers using the same earthquake records that are now scaled to the maximum credible earthquake (MCE) level to optimally determine the second slip load as well as the amount of the slippage between two slip loads. The genetic algorithm is employed to find the optimal slip loads and the amount of slippage in between. Two scenarios for height-wise variation of the DSL parameters, i.e, the slip loads and the extent of slippage, of the SMRF models are considered. In the first scenario as a practical approach, an upward decreasing pattern of slip loads along the height of the buildings is considered. In second scenario a simple search is performed to optimally identify those parameters for all floors. Furthermore, the performance of the structural models with DSL dampers are compared with those equipped with conventional single slip load systems. The results clearly demonstrate the efficiency of the proposed DSL dampers in effectively reducing the seismic response of the structures in terms of story drifts, residual drifts, absolute floor accelerations, and base shear forces in comparison to the conventional single slip load friction dampers.